Tahapan Pengambilan Keputusan (Kajian Teoritis dari James A. F. Stoner) - Johanna Tina Maylanie (Pusat Riset dan Inovasi Nasional, 2022)
The aim of this research is to describe the stages of decision making in an organization which was developed from the theory of James A. F. Stoner. This research method is qualitative with a Grounded Theory approach. Data collection techniques with documentation studies. Data transfer techniques with reduction, data presentation and drawing conclusions. The results showed: (1) decision making is the way organizations choose and use decisions based on organizational analysis. (2) stages of decision making: (a) Situation analysis: by analyzing the internal and external conditions of the organization. (b) development of alternative decisions: by formulating several (more than one) decisions that might solve organizational problems. (c) evaluation of decision alternatives: by assessing and weighing the positive and negative impacts of each decision on the organization and its resources. (4) selection of decision alternatives: by determining the best decision that will be used to improve or overcome organizational problems. (5) implementing decisions: by involving all of the organization's human resources as drivers of the organizational system.